Regional PM2.5 and asthma morbidity in an agricultural community: A panel study - Loftus, Christine; Yost, Michael; Sampson, Paul; Arias, Griselda; Torres, Elizabeth; Vasquez, Victoria Breckwich; Bhatti, Parveen; Karr, Catherine (Environmental research, 2015)
Elevated pediatric asthma morbidity has been observed in rural US communities, but the role of the ambient environment in exacerbating rural asthma is poorly understood. To investigate associations between particulate matter less than 2.5μm in diameter (PM2.5) and pediatric asthma exacerbations in an agricultural community of Washington State. School-aged children with asthma (n=58) were followed for up to 25 months with repeated measures of respiratory health. Asthma symptoms and quick-relief medication use were assessed biweekly through phone administered surveys (n=2023 interviews). In addition, subjects used home peak flow meters on a daily basis to measure forced expiratory volume in one second (FEV1) (n=7830 measurements). Regional PM2.5 was measured at a single air monitor located centrally in the study region. To assess relationships between PM2.5 and these outcomes we used linear regression with generalized estimating equations, adjusting for meteorological and temporal confounders. Effect modification by atopy was explored as well. An interquartile increase (IQR) in weekly PM2.5 of 6.7μg/m3 was associated with an increase in reported asthma symptoms Specific symptoms including wheezing, limitation of activities, and nighttime waking displayed the strongest associations. FEV1 as a percent of predicted decreased by 0.9% (95%CI: −1.8, 0.0) for an IQR increase in PM2.5 one day prior, and by 1.4% (95%CI: −2.7, −0.2) when restricted to children with atopic asthma. This study provides evidence that PM2.5 in an agricultural setting contributes to elevated asthma morbidity. Further work on identifying and mitigating sources of PM2.5 in the area is warranted. •Little is known about environmental triggers of asthma in rural, agricultural settings.•Children with asthma in an agricultural area had lower FEV1 after elevated PM2.5.•Children also reported asthma symptoms more frequently after elevated weekly PM2.5.•Results warrant increased attention to rural air pollution and pediatric asthma.